Comprehensive transcriptome profiling of urothelial cells following TNFα stimulation in an in vitro interstitial cystitis/bladder pain syndrome model - Kuret, Tadeja; Peskar, Dominika; Kreft, Mateja Erdani; Erman, Andreja; Veranič, Peter (Frontiers in Immunology, 2022)
Urothelial cells of the urinary bladder play a critical role in the development and progression of interstitial cystitis/bladder pain syndrome (IC/BPS), a chronic and debilitating inflammatory disease. Given the lack of data on the exact phenotype and function of urothelial cells in an inflammatory setting (as in IC/BPS), we performed the first in-depth characterization of these cells using RNA sequencing, qPCR, ELISA, Western blot, and immunofluorescence. After TNFα stimulation, urothelial cells in the in vitro model of IC/BPS showed marked upregulation of several proinflammatory mediators, such as SAA, C3, IFNGR1, IL1α, IL1β, IL8, IL23A, IL32, CXCL1, CXCL5, CXCL10, CXCL11, TNFAIPR, TNFRSF1B, and BIRC3, involved in processes and pathways of innate immunity, including granulocyte migration and chemotaxis, inflammatory response, and complement activation, as well as TLR-, NOD-like receptor- and NFkB-signaling pathways, suggesting their active role in shaping the local immune response of the bladder. Our study demonstrates that the TNFα-stimulated urothelial cells recapitulate key observations found in the bladders of patients with IC/BPS, underpinning their utility as a suitable in vitro model for understanding IC/BPS mechanisms and confirming the role of TNFα signaling as an important component of the associated pathology. The present study also identifies novel upregulated gene targets of TNFα in urothelial cells, including genes encoding the acute phase protein SAA, complement component C3, and the cytokine receptor IFNGR1, which could be exploited as therapeutic targets of IC/BPS. Altogether, our study provides a reference database of the phenotype of urothelial cells in an inflammatory environment that will not only increase our knowledge of their role in IC/BPS, but also advance our understanding of how urothelial cells shape tissue immunity in the bladder.